2012
DOI: 10.1152/ajpregu.00292.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-specific deletion of leptin receptors causes lethal heart failure in Cre-recombinase-mediated cardiotoxicity

Abstract: Although disruption of leptin signaling is associated with obesity as well as cardiac lipid accumulation and dysfunction, it has been difficult to separate the direct effects of leptin on the heart from those associated with the effects of leptin on body weight and fat mass. Using Cre-loxP recombinase technology, we developed tamoxifen-inducible, cardiomyocyte-specific leptin receptor-deficient mice to assess the role of leptin in regulating cardiac function. Cre recombinase activation in the heart resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 48 publications
0
17
0
1
Order By: Relevance
“…Our analyses also revealed significantly elevated numbers of apoptotic cells in hearts of obese LepR S1138 and LepR db/db mice, consistent with a reduced activation of STAT3-responsive anti-apoptotic genes [40]. Although findings in mice with systemic defects in leptin signal transduction may have been confounded by the concomitant presence of obesity and associated metabolic and inflammatory alterations, adverse cardiac remodeling after MI [42] or lethal heart failure [43] were recently reported in mice with cardiomyocyte-specific LepR deletion. On the other hand, the beneficial effects of leptin-mediated STAT3 activation may not be restricted to cardiomyocytes.…”
Section: Discussionmentioning
confidence: 68%
“…Our analyses also revealed significantly elevated numbers of apoptotic cells in hearts of obese LepR S1138 and LepR db/db mice, consistent with a reduced activation of STAT3-responsive anti-apoptotic genes [40]. Although findings in mice with systemic defects in leptin signal transduction may have been confounded by the concomitant presence of obesity and associated metabolic and inflammatory alterations, adverse cardiac remodeling after MI [42] or lethal heart failure [43] were recently reported in mice with cardiomyocyte-specific LepR deletion. On the other hand, the beneficial effects of leptin-mediated STAT3 activation may not be restricted to cardiomyocytes.…”
Section: Discussionmentioning
confidence: 68%
“…Disruption of these leptin signaling pathways causes dilated cardiomyopathies (21,24,26). Previous studies from our laboratory and others have also demonstrated the protective role of leptin against the development of heart failure, and this appears to be mediated at least in part by cardiac metabolic effects (17,32). In the present study, we demonstrated significant increases in p-STAT3 and STAT3 in the hearts of db/db-cardiac LepR rescue mice compared with db/db mice and lean controls, indicative of increased leptin signaling in the hearts of these mice.…”
Section: Discussionmentioning
confidence: 71%
“…Echocardiographic assessment of cardiac function was conducted using a Vevo 770 High Resolution In Vivo Imaging System (Visualsonics, Toronto, ON, Canada), as described previously (16,17). Measurements were made with a 710B RMV scanhead with a center frequency of 25 MHz.…”
Section: Methodsmentioning
confidence: 99%
“…Leptin signalling has been shown to have an important role in maintaining ATP formation because knockout of leptin in stressed mice is lethal (Hall et al . ). Thus, in the setting of HF, leptin may help, amongst other plausible mechanisms, to refill the SR with Ca 2+ , providing ATP to the SERCA pump or by increasing SERCA expression levels, which are known to be reduced in HF (Hobai & O'Rourke, ).…”
Section: Discussionmentioning
confidence: 97%